Penerapan Pembelajaran Berbasis Literasi untuk Meningkatkan Kemampuan Membaca dan Menulis Siswa Kelas 3 SD: Studi Literatury: Penerapan Pembelajaran Berbasis Literasi untuk Meningkatkan Kemampuan Membaca dan Menulis Siswa Kelas 3 SD: Studi Literatur - Sairotul fadhilah (Jurnal Dharma PGSD, 2025)
Abstract: Low interest in reading and writing hinders the improvement of literacy skills among students in Indonesia. This study examines a literacy-based learning model to enhance the reading and writing abilities of third-grade elementary students through a qualitative literature review. Literature was selected from Google Scholar published within the last five years and analyzed using a synthesis matrix. The results indicate that active learning models, engaging media, and collaboration between teachers and parents effectively improve students' literacy. Additionally, technology and literacy programs support the development of a sustainable reading culture. This study serves as a reference for curriculum development and innovative teaching methods at the elementary level. Keywords: learning, literacy, reading ability, writing ability, grade 3 elementary school